Application of Repacking Design to Improve Performance and Brand Awareness of Griya YKM Cinere Products, Depok City - Gunaedi A, Jenji; Nastiti, Heni; Astuti, Miguna; DM, Bernadin (Indonesian Journal of Society Development, 2024)
Small and Medium Enterprises (SMEs) are the backbone of the national economy. They are capable of driving the community economic growth and absorbing a large workforce. Despite the quality of products produced by SMEs being on par with those from manufacturers, the simple packaging often makes these products less attractive, limiting market reach and competitiveness. This issue is compounded by the lack of understanding and skills among SMEs regarding the importance of packaging design and how to redesign currect packaging to make the products itself more attractive. This community service innitiative aimed to address these issues through socialization efforts that emphasized the significance of packaging design and the need for attractive product packaging redesign. Pre-test and post-test results conducted before and after the socialization indicated an increased understanding among participants about the importance of packaging design and redesigning, which can enhance consumer interest and boost sales